Compound[ing] disasters in Puerto Rico: Pathways for virtual transdisciplinary collaboration to enhance community resilience. (September 2022) - Stablein, M.J.; Gonzalez Cruz, J.; Fidan, E.N.; Talbot, J.; Reed, S.P.; Walters, R.S.; Ogunyiola, A.J.; Fernández Frey, M.; Ramirez, M.; Rosado Casanova, B.; Heemstra, J.; Marshall, A.; et al.
Graphical abstract: Highlights: Novel virtual research is needed to address the complexity of compounding disasters. Remote transdisciplinary team engages participatory action research in Puerto Rico. Citizen science enhances NGO data pathways and socioenvironmental resilience. Interactive mapping elucidates opportunities for community-based disaster solutions. Lessons learned are offered on the iterative process and high-performance teaming. Abstract: Puerto Rico has been subject to complex and compounding effects of multiple disasters, exacerbated by sociopolitical, climactic, and geographical challenges that complicate relief and resilience. Interdisciplinary teams are uniquely suited to traverse emerging challenges in post-disaster settings, but there are few studies that leverage transdisciplinary skill sets and virtual co-production of knowledge to build on local autonomous responses. Communities are key sources of information and innovation which can serve as a model for recovery amidst disaster. Thus, an interdisciplinary team of emerging scholars collaborated with Caras con Causa, a local organization in Cataño, Puerto Rico, to develop processes for enhancing autonomous responses to disaster events through participatory pathways, specifically highlighting local knowledge and preferences. The results of this collaboration include: (1) an iterative process model for transdisciplinary co-production in virtual settings and (2) key highlights from post engagement reflections including community-scale definitions of disaster, and limitations to virtual collaboration amidst disaster. Together, these results yielded critical insights and lessons learned, including recommendations for improved project communication methods within transdisciplinary and virtual collaborations. Collectively, the process, it's resulting products, and the post-engagement reflections demonstrate a pathway for scholars and community members to engage disaster resilience challenges. These strategies are most effectively practiced through focused collaboration with community stakeholders and are paramount in solving real-world challenges related to the increasing complex of compounding disasters.